2021
DOI: 10.3390/ijms222212442
|View full text |Cite
|
Sign up to set email alerts
|

Iron Homeostasis Disorder and Alzheimer’s Disease

Abstract: Iron is an essential trace metal for almost all organisms, including human; however, oxidative stress can easily be caused when iron is in excess, producing toxicity to the human body due to its capability to be both an electron donor and an electron acceptor. Although there is a strict regulation mechanism for iron homeostasis in the human body and brain, it is usually inevitably disturbed by genetic and environmental factors, or disordered with aging, which leads to iron metabolism diseases, including many n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 168 publications
(244 reference statements)
3
59
0
1
Order By: Relevance
“…Ferritin in the cerebrospinal fluid (CSF) of AD patients has been shown significantly increased, which is negatively correlated with cognitive decline and hippocampal atrophy in AD ( Diouf et al, 2019 ). Additionally, iron can enter mitochondria to form iron sulfur cluster and participate in participate in the process of aerobic respiration ( Peng et al, 2021 ).…”
Section: Iron Metabolism In Healthy and Alzheimer’s Disease Brainmentioning
confidence: 99%
“…Ferritin in the cerebrospinal fluid (CSF) of AD patients has been shown significantly increased, which is negatively correlated with cognitive decline and hippocampal atrophy in AD ( Diouf et al, 2019 ). Additionally, iron can enter mitochondria to form iron sulfur cluster and participate in participate in the process of aerobic respiration ( Peng et al, 2021 ).…”
Section: Iron Metabolism In Healthy and Alzheimer’s Disease Brainmentioning
confidence: 99%
“…There is a close connection between iron homeostasis and the pathology of AD. It has been reported that the translation of amyloid precursor protein APP is directly regulated by cellular iron levels [ 93 ]. Most of the APP is cleaved by a nonamyloid production pathway.…”
Section: Iron Metabolism and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In contrast, iron deficiency increases the activity of furin, which enhances α-secretase and stimulates the nonamyloid production pathway [ 95 ]. Iron may regulate APP processing through IRPS, interacting with the hypothetical IRE in the 5′- untranslated region of APP mRNA [ 93 ]. The translation of APP may therefore be up-regulated under the condition of iron excess, increasing the amount of APP available to enter the amyloid production pathway, thereby resulting in the aggregation of Aβ peptide [ 93 ].…”
Section: Iron Metabolism and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Currently, mounting evidence indicates that the accumulation of abnormal proteins such as Aβ and p-Tau is closely associated with the dysfunction of the protein quality control system in the brain [ 21 ]. Particularly in the early stage of AD, the synthesis, degradation and removal of essential biology components in the protein quality control system changes, suggesting that the protein quality control system may be a new and potential target of AD therapy [ 22 ].…”
Section: Introductionmentioning
confidence: 99%